Seasonal cycle and source analyses of aerosol optical properties in a semi-urban environment at Puijo station in Eastern Finland - A. Leskinen; A. Arola; M. Komppula; H. Portin; P. Tiitta; P. Miettinen; S. Romakkaniemi; A. Laaksonen; K. E. J. Lehtinen (Atmospheric Chemistry and Physics, 2012)
We introduce a four-year (in 2006–2010) continuous data set of aerosol optical properties at Puijo in Kuopio, Finland. We study the annual and diurnal variation of the aerosol scattering and absorption coefficients, hemispheric backscattering fraction, scattering Ångström exponent, and single scattering albedo, whose median values over this period were 7.2 Mm−1 (at 550 nm), 1.0 Mm−1 (at 637 nm), 0.15, 1.93 (between 450 and 550 nm), and 0.85, respectively. The scattering coefficient peaked in the spring and autumn, being 2–4 times those in the summer and winter. An exception was the summer of 2010, when the scattering coefficient was elevated to ~300 Mm−1 by plumes from forest fires in Russia. The absorption coefficient peaked in the winter when soot-containing particles derived from biomass burning were present. The higher relative absorption coefficients resulted in lower single scattering albedo in winter. The optical properties varied also with wind direction and time of the day, indicating the effect of the local pollutant sources and the age of the particles. Peak values in the single scattering albedo were observed when the wind blew from a paper mill and from the sector without local pollutant sources. These observations were linked, respectively, to the sulphate-rich aerosol from the paper mill and the oxygenated organics in the aged aerosol, which both are known to increase the scattering characteristics of aerosols. Decreases in the single scattering albedo in the morning and afternoon, distinct in the summertime, were linked to the increased traffic density at these hours. The scattering and absorption coefficients of residential and long-range transported aerosol (two separate cloud events) were found to be decreased by clouds. The effect was stronger for the scattering than absorption, indicating preferential activation of the more hygroscopic aerosol with higher scattering characteristics.